The role of grazers in early-life stages of Cystoseira sensu lato can be crucial in the restoration of marine forests - Monserrat, Margalida; Verdura, Jana; Comeau, Steeve; Cottalorda, Jean-Michel; Priouzeau, Fabrice; Romero, Gilbers; Mangialajo, Luisa (Frontiers in Marine Science, 2023)
Grazing is one of the most important biological factors controlling the abundance of early-life stages of fucoids and one of the major issues when restoring marine forests. Benthic macroinvertebrates (e.g., sea urchins) and fish shape and regulate benthic macroalgal communities from polar to tropical regions, and can be responsible for regime shifts leading to the predominance of turfs and/or barren grounds. However, other herbivores (i.e., mesograzers) could also significantly participate in the grazing, especially on early-life stages, hampering the persistence and capacity of Cystoseira sensu lato populations to recover after major disturbances and being a cause of failure of restoration actions. We performed experiments in the field and in mesocosm in order to investigate the herbivory pressure and the effects of different grazers on recruits of Cystoseira compressa. The results highlight that non-strict herbivorous invertebrates, such as Clibanarius erythropus, Cerithium vulgatum and Idotea balthica, graze on recruits of Cystoseira s.l. spp., with I. balthica showing the highest consumption rate. We concluded that biotic factors such as herbivory, that affect key life stages, can be crucial for the conservation of Cystoseira s.l. forests and need to be better understood and considered on a case-by-case basis when planning restoration actions.